Characterization and frequency of failure of the Peritoneal Dialysis technique in diabetic patients - Dra. Alejandra Arévalo Becerril; Dr. Eduardo Daniel Anica Malagón; Juana Citlali De la Torre García; Karla Murillo-Villanueva; Dra. Clarita Josselin Cabrera Juárez; Dra. Andrea Carolina Loyo Mejía; Dr. José Antonio Lara Buenabad (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Diabetes is defined as a disease caused by alterations in carbohydrate metabolism with multi-organ complications; diabetic nephropathy is one of the main causes of End-Stage Chronic Kidney Disease in Mexico and the world, having a 10-fold increased risk of nephropathy. PD is an option in low-income countries, as it is cost-effective when performed at home vs. in health institutions with similar benefits for the first 1 to 2 years. However, despite its benefits, PD is not without complications, one of the main ones being FT, defined as the transfer of the patient to HD due to the ineffectiveness of PD in maintaining adequate renal replacement therapy. FT can be caused by a variety of factors such as recurrent peritoneal infections, mechanical catheter problems, and complications related to ultrafiltration. Due to the constant increase in the incidence of DM and ESCT as well as the controversy in the literature on the outcomes of patients living with diabetes in PD, it is important to be able to characterize and calculate the frequency of TF in PD in diabetic patients, in order to be able to seek a route of improvement in actions at different levels. both institutional, health personnel and family members. Objective: The aim of the study is to evaluate the outcome in the subgroup of diabetic patients who started PD between 2020-2021 and to detect the frequency of PD in order to characterize and detect associated risk factors. Material and Methods: We designed an observational, retrospective, analytical, and longitudinal study, whose objective was to obtain the incidence of PD in diabetic patients with ESRD in a tertiary hospital, in order to identify risk factors. Inclusion criteria: Adults over 18 years of age with a diagnosis of Type 2 Diabetes Mellitus prior to the diagnosis of ESRD, who have started renal replacement therapy in the PD modality at the Tertiary Level Hospital, between 2020 and 2021; (N=131). For the Absolute frequencies and percentages were calculated for qualitative variables; for quantitative variables, such as age, normal distribution was determined using the Kolmogorov-Smirnov test (p >0.05), so mean and standard deviation were used. To know the differences in the characteristics based on the failure or not of the technique, the χ2 test (Fisher’s exact test in case of having a square with an expected count <5) and for the numerical variable Student’s t-test for independent samples were used. A value of p <0.05 was considered to be of statistical significance. To identify the risk factors associated with failure of the technique, an unadjusted logistic regression model was performed and adjusted for the same variables (PD modality, PD-associated infection, type of hospitalization), with the intro method, and odds ratio (OR) and 95% confidence interval (95% CI) were obtained. Results: The average age was 54 years; with the following distribution of percentage of type of schooling, primary 52.7% and secondary 35.2%. The main comorbidity found is Systemic Arterial Hypertension with a frequency of 98%, followed by diabetic/hypertensive retinopathy in 90.1%. A dialysis emergency reason for admission was 58.2% of patients at the time of peritoneal dialysis catheter placement. Of the total sample (N=91), 70.3% had failure of the peritoneal dialysis technique; The main etiology was catheter-associated infection (41.8%), followed by mechanical dysfunction (16.5%). The most commonly used type of dialyzer solution was dialysis solution with 1.5% glucose (78%). The risk factors associated with FT are IPD in the unadjusted model (OR of 20.8; CI 4.52-95.88, p<0.001) and in adjusted multivariate model) OR 35.96; CI 6.81189.64, p< 0.001) and catheter-associated infection with an OR of 16.07 (CI 3.5-73.67, p<0.001) and multivariate adjustment OR of 29.35 (CI 5.48-157.62 p<0.001) remaining risk factors for technique failure. Conclusions: PD in PD in diabetic patients has a statistically significant relationship with the IPD modality, as well as catheter-associated infection in unadjusted and multivariate adjustment analysis. The choice of dialyzer solution in diabetic patients should be personalized and with a tendency to use glucose-free solutions to improve peritoneal functionality in PD. Education of patients, family members, and personnel in charge of managing PD modalities is an area of opportunity for constant improvement of PD and reducing FT.